Children’s and Caregiver´s Mental Health and associated factors during COVID-19 Pandemic - Nóblega, Magaly (2024)
Mental health indicators of children from 6 to 71 months and their caregivers, and their associated factors, are described during the pandemic context. The information was collected through an ad hoc survey answered by 59,113 caregivers from the 24 departments and the constitutional province of Peru. A significant presence of externalizing behavior problems was reported in boys and girls. 8 out of 10 caregivers reported one or two indicators of anxiety, and around 2 out of 10 caregivers reported feeling stressed on many occasions and be alone in their parenting role. Practical implications for childhood interventions and parenting support are discussed based on the results.